The illegal sale of cigarettes to US minors: estimates by state. - Cummings, K M (1994)
Data available from recent national surveys on the cigarette consumption and purchasing practices of teenage smokers were used to generate state-specific estimates of the number of teenage smokers and cigarette sales to minors. In 1991, approximately 2.7 million teenage cigarette smokers consumed an average of 28.3 million cigarettes per day (516 million packs per year). An estimated 255 million packs of cigarettes were sold illegally to minors in 1991. To make cigarettes and other tobacco products less accessible to minors, policymakers should consider implementing various legislative and economic measures such as banning cigarette vending machines and raising tobacco excise taxes.